The control system for special preparedness of cyclists - A.N. Kolumbet; L.Y. Dudorova; N.A. Babina; T.A. Bazulyuk; N.Y. Maximovich (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to develop a system for monitoring the level of special preparedness of cyclists (specialized in individual race for 4 km) on the basis of the indicators of the cardiorespiratory system. Material: The study involved bicyclists (n=14, age 18-22 years). Results: The step-increasing load to the full allows to determine the maximum functional opportunities of the body of cyclists. The coefficient of efficiency of the functioning of the cardiovascular system is equal to the ratio of the average distance value of the pulse to the maximum value of the pulse. Using the linear regression equation, it is possible to predict the magnitude of the pulse at a given speed of movement. Conclusions: It is possible to find out the individual characteristics of athletes with the help of an indicator of the effectiveness of the functioning of the cardiovascular system. One can compare the activity of the cardiovascular system of athletes of different qualifications, different age groups, gender, level of preparedness. The degree of realization of the functionality of cyclists is calculated by a special formula and serves to monitor the training and competitive process. The results of the studies make it possible to predict the result by evaluating the level of special physical preparation.